Detection of RTX Toxin Gene in Vibrio cholerae by PCR - Chow, K. H. (American Society for Microbiology, 2001)
A PCR that amplifies a recently discovered Vibrio cholerae RTX (repeat in toxin) toxin gene was developed. Among 166 clinical and environmental isolates of V. cholerae causing epidemics and sporadic cases of cholera in various parts of the world, all were found to be toxigenic by both PCR and HEp-2 cell cytotoxicity assay. Standard strains of the classical biotype containing a deletion within the gene cluster exhibited negative results by both assays. This is the first rapid genotyping method for differentiation of V. cholerae O1 classical biotype strains from El Tor biotype strains as well as strains of other non-O1 serogroups including serogroup O139. The PCR assay that was developed also specifically detects RTX toxin genes in V. cholerae, as clinical isolates of Vibrio parahaemolyticus, diarrheagenic Escherichia coli, Aeromonas species, and Plesiomonas species were all negative by the RTX toxin-specific PCR as well as the HEp-2 cytotoxicity assay. These findings highlight the characteristics of the RTX toxins in V. cholerae. Their role in the pathogenicity of the bacterium requires further investigation.